Always different?: exploring the monstrous-feminine and maternal embodiment in organisation - Vachhani, Sheena J (Equality, Diversity and Inclusion: An International Journal, 2014)
Purpose – The purpose of this paper is to problematise the notion of woman-as-monster and draws together a conceptual analysis of the monstrous-feminine and its relation to maternal and monstrous bodies including its implications for equality and inclusion in the workplace. Design/methodology/approach – Whilst exploring how female monsters are inextricably tied to their sexual difference, the author draws on social and psychoanalytic perspectives to suggest how such monstrosity is expressed through ambivalence to the maternal. The author analyses two “faces” of the monstrous-feminine in particular: the archaic mother and the monstrous womb (Creed, 1993) and develop this discussion in relation to the potential for a feminist monstrous politics of organisation. Findings – First, the author exposes the basis on which the monstrous-feminine articulates and disarticulates femininity, that is to say, how a feminist analysis of monsters may enable but also foreclose a positive articulation of disruption, disorder and disorganisation central to the conceptualisation of monsters. This is done through a reading of the maternal-feminine and literature on motherhood in organisation studies. Second, the author locates the monstrous-feminine in the body and explores how maternal bodies are constructed and experienced as monstrous as they disrupt the self/other relationship. This analysis suggests that embodying the monster comes with risks and that different configurations of the monstrous maternal are necessary for equality and inclusion in the workplace. Originality/value – The paper identifies and contributes to growing research on the ambivalence of monsters and expands a neglected area of the feminine and maternal aspects of these relationships and what this means for workplace relations.